Demographic structure in Northern Ireland and its implications for constitutional preference - Jardine, Edgar F. (Statistical and Social Inquiry Society of Ireland, 1994)
An awareness of the dynamics of demographic change is fundamental to the provision of public services and an indispensable weapon in the armoury of the policy-maker. Demographic structure as reflected in the shape of a population pyramid can be a sensitive indicator of socio-economic circumstances and is thus a telling sign of need for service provision and public expenditure priorities. The point is well illustrated at the extremes if, for example, the population pyramid for the Philippines is compared with that for the United Kingdom (Figure 1). The former has a high proportion of young people with consequential need for education and child care services and a burgeoning workforce while the UK and many other Western countries anticipate a rapidly increasing number of elderly people in the population being sustained by a contracting workforce. Northern Ireland (NI) and the Republic of Ireland (Rol) share broadly similar demographic structures with a high proportion of young people (particularly in the Rol) and fewer elderly (Figure 2) and thus contrast with those of other countries in the European Union where an ageing population tends to be the norm. However, within Northern Ireland the changing demographic structures within the two main religious traditions are of additional interest because of the constitutional preferences assumed to be associated with each. The paper will therefore take an historical view of the changing balance between the two communities, assess their relative size as measured in the 1991 Census of Population, which estimated the population of Northern Ireland as a whole at just under 1,580,000, and attempt to project how the balance might change in the future. Finally, the paper will draw on data from a range of sources to explore the links between religious affiliation and constitutional preferences.
Read before the Society, 5 May 1994
Keywords: Demographic change, Northern Ireland; Religious affiliation, Northern Ireland; Northern Ireland; Demography, Northern Ireland; 314.15